The assessment of neuromuscular fatigue during 120 min of simulated soccer exercise - Goodall, S.; Thomas, K.; Harper, L. D.; Hunter, R.; Parker, P.; Stevenson, E.; West, D.; Russell, M.; Howatson, G. (European Journal of Applied Physiology, 2017)
Purpose: This investigation examined the development of neuromuscular fatigue during a simulated soccer match incorporating a period of extra time (ET) and the reliability of these responses on repeated test occasions. Methods: Ten male amateur football players completed a 120 min soccer match simulation (SMS). Before, at half time (HT), full time (FT), and following a period of ET, twitch responses to supramaximal femoral nerve and transcranial magnetic stimulation (TMS) were obtained from the knee-extensors to measure neuromuscular fatigue. Within 7 days of the first SMS, a second 120 min SMS was performed by eight of the original ten participants to assess the reliability of the fatigue response. Results: At HT, FT, and ET, reductions in maximal voluntary force (MVC; -11, -20 and -27%, respectively, P = 0.01), potentiated twitch force (-15, -23 and -23%, respectively, P < 0.05), voluntary activation (FT, -15 and ET, -18%, P = 0.01), and voluntary activation measured with TMS (-11, -15 and -17%, respectively, P = 0.01) were evident. The fatigue response was robust across both trials; the change in MVC at each time point demonstrated a good level of reliability (CV range 6-11%; ICC2,1 0.83-0.94), whilst the responses identified with motor nerve stimulation showed a moderate level of reliability (CV range 5-18%; ICC2,1 0.63-0.89) and the data obtained with motor cortex stimulation showed an excellent level of reliability (CV range 3-6%; ICC2,1 0.90-0.98). Conclusion: Simulated soccer exercise induces a significant level of fatigue, which is consistent on repeat tests, and involves both central and peripheral mechanisms.